Biochar application : essential soil microbial ecology - Ralebitso-Senior, T. Komang; Orr, Caroline H. (Amsterdam, Netherlands : Elsevier, 2016)
Biochar Application: Essential Soil Microbial Ecology outlines the cutting-edge research on the interactions of complex microbial populations and their functional, structural, and compositional dynamics, as well as the microbial ecology of biochar application to soil, the use of different phyto-chemical analyses, possibilities for future research, and recommendations for climate change policy. Biochar, or charcoal produced from plant matter and applied to soil, has become increasingly recognized as having the potential to address multiple contemporary concerns, such as agricultural productivity and contaminated ecosystem amelioration, primarily by removing carbon dioxide from the atmosphere and improving soil functions. Biochar Application is the first reference to offer a complete assessment of the various impacts of biochar on soil and ecosystems, and includes chapters analyzing all aspects of biochar technology and application to soil, from ecogenomic analyses and application ratios to nutrient cycling and next generation sequencing. Written by a team of international authors with interdisciplinary knowledge of biochar, this reference will provide a platform where collaborating teams can find a common resource to establish outcomes and identify future research needs throughout the world.
Chapter 1. Microbial Ecology Analysis of Biochar-Augmented Soils: Setting the Scene -- Chapter 2. Feedstock and Production Parameters: Effects on Biochar Properties and Microbial Communities -- Chapter 3. Biochar Effects on Ecosystems: Insights From Lipid-Based Analysis -- Chapter 4. DGGE-Profiling of Culturable Biochar-Enriched Microbial Communities -- Chapter 5. Next-Generation Sequencing to Elucidate Biochar-Effected Microbial Community Dynamics -- Chapter 6. Examining Biochar Impacts on Soil Abiotic and Biotic Processes and Exploring the Potential for Pyrosequencing Analysis -- Chapter 7. Elucidating the Impacts of Biochar Applications on Nitrogen Cycling Microbial Communities -- Chapter 8. Microbial Ecology of the Rhizosphere and Its Response to Biochar Augmentation -- Chapter 9. Potential Application of Biochar for Bioremediation of Contaminated Systems -- Chapter 10. Interactions of Biochar and Biological Degradation of Aromatic Hydrocarbons in Contaminated Soil -- Chapter 11. A Critical Analysis of Meso- and Macrofauna Effects Following Biochar Supplementation -- Chapter 12. Summation of the microbial ecology of biochar application.
Print version record.
Includes index.
Includes bibliographical references at the end of each chapters and index.
Keywords: Biochar; Soil microbial ecology; SCIENCE -- Life Sciences -- Biology; SCIENCE -- Life Sciences -- Microbiology; Biochar; Soil microbial ecology; Electronic books